Andalusia: Sebuah kepingan yang hilang dari perjalanan panjang kejayaan Islam di Benua Afrika - Muchofifah, Azza Rukyatul (Maliki Interdisciplinary Journal, 2024)
Andalusian Islam is one part of the glorious history of Islam, where civilization and culture developed rapidly from Andalusia to the European continent. Andalusia or now known as Spain keeps a long history of the struggle of Muslims in spreading religion, as well as the history of how Islam also collapsed there. Andalusia was once the center of civilization, culture, and science in Europe and Africa in the Middle Ages before experiencing a decline due to poor governance. The writing of this article itself uses the historical method. Where data collection and sources are based on library research or Library Research. Both use books and printed literature such as journals and relevant online literature as reference materials in the preparation of this article. This article was written to provide an overview of how Islam entered Andalusia and how Islam ended in Andalusia. Where Islam entered Andalusia after going through a long journey and battle, until under the leadership of Tariq bin Ziyad Islam succeeded in controlling Andalusia. But unfortunately Islam has experienced a setback since 1013 which was marked by the abolition of the position of Caliph and the